2015
DOI: 10.1002/jso.23890
|View full text |Cite
|
Sign up to set email alerts
|

Utility of sentinel lymph node biopsy for solitary dermal melanomas

Abstract: Background and Objectives Solitary dermal melanoma (SDM) is melanoma confined to subcutaneous and/or dermal layers in the absence of a known primary cutaneous lesion. We hypothesized that sentinel node biopsy is an effective staging strategy for this rare disease. Methods A Markov decision model was constructed to represent two management strategies for SDM: wide local excision followed by observation, and wide local excision followed by sentinel node biopsy. Utilities, likelihood of positive sentinel node b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…They constructed a Markov model to compare management strategies of WE of DM with and without the use of SLNB. The authors concluded patients in the SLNB arm were more likely to remain in the disease‐free state compared to those who had a WE followed by observation alone . In the final analysis of the MSLT‐1 trial, patients with intermediate thick melanomas (1.2–3.5 mm) who were randomized to SLNB had a significant improvement in relapse‐free survival compared to those in the observation arm ( P = 0.01) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They constructed a Markov model to compare management strategies of WE of DM with and without the use of SLNB. The authors concluded patients in the SLNB arm were more likely to remain in the disease‐free state compared to those who had a WE followed by observation alone . In the final analysis of the MSLT‐1 trial, patients with intermediate thick melanomas (1.2–3.5 mm) who were randomized to SLNB had a significant improvement in relapse‐free survival compared to those in the observation arm ( P = 0.01) .…”
Section: Discussionmentioning
confidence: 99%
“…They constructed a Markov model to compare management strategies of WE of DM with and without the use of SLNB. The authors concluded patients in the SLNB arm were more likely to remain in the disease-free state compared to those who had a WE followed by observation alone [19]. In the final analysis of the MSLT-1 trial, patients with…”
Section: Discussionmentioning
confidence: 99%
“…In this study, primary dermal melanoma is defined as a melanoma (collection of atypical melanocytes that are pleomorphic, often mitotically active) within the dermis without overlying melanoma in situ from which it is arising, in the absence of evidence that this is a metastasis from another primary melanoma. Primary dermal melanoma is thought to represent about 0.4%‐0.9% of all melanomas . These tumors may be a unique subtype of melanoma, distinct from dermal metastases .…”
Section: Introductionmentioning
confidence: 99%
“…When compared with cutaneous lesions, these lesions have similar prognostic characteristics as intermediate‐thickness primary cutaneous melanomas . There is evidence that SLNB for primary dermal melanoma has utility compared to excision alone …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation